From Poetry As the Excess of Language to Poems Generated by Artificial Intelligence (Poet As Researcher in the World of New Cultural Paradigms) - Strehovec, Janez (Canadian Journal of Language and Literature Studies, 2023)
Beuys' expanded concept of the artwork is also relevant in poetry, where we can see the expansion of poetry into other fields and new media; poems can be found in the sky, in space, on the skin of performers, on facades, in the sand, in the snow and in the digital medium, where we also encounter AI-generated poetry. Poetry is contextualised, integrated into the social, alongside esoteric searches towards minimalist texts that can be read by machines or disappear in the process of being read, we encounter poetry in social media and as excellent content in prime time TV shows (Million's poet competition in the United Arab Emirates, from 2007 to the present). In this text we are interested in poetry as research, complementary to research in other fields, which means that we can also understand poetry in terms of cognitive activity and the poet as cognitive worker. We also pay attention to experimental explorations in the temporary poetry, which conflict with the tendency to situate such researches in the printed book. AI-generated texts are something other than poetry understood as an excess of language, the work of a corporeal poet with emotions, experiences and passions.